Assessment Scale for Tic Disorders in Children - Hou Yongmei (Disease and Health: Research Developments Vol. 4, 2025)
Background: Tic disorders can cause damage to children’s learning, daily life, and social function. The severity of the damage is usually evaluated quantitatively using standardized scales. Objective: The objective of the study is to understand the main methods used in the screening and diagnosis of childhood tic disorders (CTD), with a focus on the content and psychometric properties of commonly used scales. On this basis, the application and prospects of scales are proposed. Methods: The literature retrieval method was used to search Empirical papers published in English or Chinese in the past 35 years from Pubmed, Google Scholar, CNKI and Wanfang databases. Results: Thirty-one articles were included. CTD assessment scales are divided into diagnostic and screening scales. The Yale Global Tic Severity Scale (YGTSS) is the most commonly used diagnostic scale and can be considered the gold standard for CTD assessment. Conclusion: The development of CTD assessment scales is becoming increasingly in-depth and widely used, making them an effective tool for CTD diagnosis and screening. The combination of scale assessment and instrumental detection such as electroencephalography is the direction of CTD diagnosis.